Christian-Muslim Encounter in Freetown in the Nineteenth Century: Implications for Interfaith Engagement - Sanneh, Lamin O. (Piety and power: Muslims and Christians in West Africa, 1996)
xv, 207 p. ; 24 cm; Includes bibliographical references (p. 175-195) and index
free
Keywords: Islam – Africa; West